X Meeting of The Latin American Society of Tuberculosis and other Mycobacteriosis (SLAM-TB) - X SLAM-TB 2021, Meeting (Revista Bio Ciencias, 2021)
On behalf of the Mexican Society of Immunology (SMI), and the Latin-American Society of Tuberculosis and other Mycobacteriosis (SLAM-TB), it is a pleasure to invite and welcome you to the XXIV Congress of SMI and X Meeting of the SLAM-TB, which in this occasion and for the first time both Conferences will be virtual events. Monterrey city in the Northeast of Mexico was the original place where both Conferences should be held the last year, but due to the COVID-19 pandemic it was not possible and now both Congresses will be virtual meetings. Both Scientific Program Committees have organized an outstanding schedule of lectures and symposia that will provide you with the fundamental knowledge and the most recent advances in mycobacteriology and immunity in health and disease. Due to the solidarity and enthusiasm of our invited speakers, the new program is quite similar to the original one and in the case of the Mexican Congress of Immunology it was substantially improved by the participation of Dr. Buchner and Dr. Doherty, both Medicine Nobel Prize awarded scientists. Besides the integration of new symposiums of high relevance topics organized by colleagues with high academic profile and prestige. SLAMTB congregate a wide group of Latin-American microbiologists, molecular biologists, epidemiologists, immunologists and other researchers interested in the study of Mycobacterium tuberculosis and other related pathogens. SLAM-TB was founded in 2006 in Pucón Chile and its most important academical activity is this Meeting, in which numerous and active researchers in this field from diverse countries present and discuss their recent results, also well-known excellent researchers dictate conferences on the most relevant topics about tuberculosis.